The Effectiveness of Physical Therapy in Children with Autism - Radosław Sroka (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2014)
The main aim of the work was to evaluate the effectiveness of physical therapy conducted with autistic children from the kindergarten at Krzemienna 42B in Szczecin. The research was conducted in the first halves of 2009 and 2010. The diagnostic tool used in order to evaluate gross motor skills was psycho-educational profile – revised (PEP-R). The research group included 8 boys with medically certified autism spectrum disorder. In 2009, out of 126 tasks given, all the tested students performed 104 tasks evaluated as completed, 16 tasks evaluated as promising and 6 tasks evaluated as uncompleted. Only one boy performed all tasks properly. In 2010 the students performed 120 tasks evaluated as completed, 5 as promising and 1 as uncompleted. Four of the autistic boys performed the tasks they were given perfectly. In 2009 the biological age of most tested children was higher than the developmental age in the scope of gross motor skills. Implementing new, individual therapeutic programs based, among other things, on TEEACH tasks, helped to significantly level out the differences.